Frontier House [videorecording (DVD)] - Brown, Nicolas Roether; Chermayeff, Maro; Walker, Kathryn. 1943- (PBS Video, 2002)
Three modern families were chosen to learn to survive as if the year is 1883. Using the tools and technology of that time they must make difficult choices and cope with the consequences in the Montana wilderness.